Immune Responses Elicited by Outer Membrane Vesicles of Gram-Negative Bacteria: Important Players in Vaccine Development - Branko Velimirov; Branko Alexander Velimirov (Life, 2024)
The attractiveness of OMVs derived from Gram-negative bacteria lies in the fact that they have two biomembranes sandwiching a peptidoglycan layer. It is well known that the envelope of OMVs consists of the outer bacterial membrane [OM] and not of the inner one [IM] of the source bacterium. This implies that all outer membranous molecules found in the OM act as antigens. However, under specific conditions, some of the inner membrane proteins can be exported into the outer membrane layer and perform as antigens. A key information was that the used purification procedures for OMVs, the induction methods to increase the production of OMVs as well as the specific mutant strains obtained via genetic engineering affect the composition of potential antigens on the surface and in the lumen of the OMVs. The available literature allowed us to list the major antigens that could be defined on OMVs. The functions of the antigens within the source bacterium are discussed for a better understanding of the various available hypotheses on the biogenesis of vesicle formation. Also, the impacts of OMV antigens on the immune system using animal models are assessed. Furthermore, information on the pathways of OMVs entering the host cell is presented. An example of a bacterial infection that causes epidemic diseases, namely via Neisseria meningitidis, is used to demonstrate that OMVs derived from this pathogen elicit protective immune responses when administered as a vaccine. Furthermore, information on OMV vaccines under development is presented. The assembled knowledge allowed us to formulate a number of reasons why OMVs are attractive as vaccine platforms, as their undesirable side effects remain small, and to provide an outlook on the potential use of OMVs as a vaccine platform.